A Review of Current Methods for Analysis of Mycotoxins in Herbal Medicines - Zhang, Lei (Toxins (Basel), 2018)
The presence of mycotoxins in herbal medicines is an established problem throughout the entire world. The sensitive and accurate analysis of mycotoxin in complicated matrices (e.g., herbs) typically involves challenging sample pretreatment procedures and an efficient detection instrument. However, although numerous reviews have been published regarding the occurrence of mycotoxins in herbal medicines, few of them provided a detailed summary of related analytical methods for mycotoxin determination. This review focuses on analytical techniques including sampling, extraction, cleanup, and detection for mycotoxin determination in herbal medicines established within the past ten years. Dedicated sections of this article address the significant developments in sample preparation, and highlight the importance of this procedure in the analytical technology. This review also summarizes conventional chromatographic techniques for mycotoxin qualification or quantitation, as well as recent studies regarding the development and application of screening assays such as enzyme-linked immunosorbent assays, lateral flow immunoassays, aptamer-based lateral flow assays, and cytometric bead arrays. The present work provides a good insight regarding the advanced research that has been done and closes with an indication of future demand for the emerging technologies.